Pembingkaian Pemberitaan Nonton Bareng Film G30S/PKI di Media Daring - Luthfian Khoironi; Rana Akbari Fitriawan (Ultimacomm: Jurnal Ilmu Komunikasi, 2018)
This research aims to see the framing of G30S/PKI (Treachery of the Communist Party) film screening on two online media, Detik.com and Kompas.com, in September 2017. Qualitative data is compiled and analyzed in a constructivism perspective, using the model of Zhongdang Pan and Kosicki. The result shows Detik.com tends to frame the film screening as a proper thing to be done, while Kompas.com tends to present the film screening inappropriate. This study results in a significant difference in the way Kompas.com and Detik.com framed the news of the film screening in the same period. Keywords: News, online media, film screening, G30SPKI, mass media construction